2021
DOI: 10.1111/hepr.13671
|View full text |Cite
|
Sign up to set email alerts
|

Easy albumin–bilirubin score as a new prognostic predictor in hepatocellular carcinoma

Abstract: Background: Liver functional reserve is a major prognostic determinant in patients with hepatocellular carcinoma (HCC). The albumin-bilirubin (ALBI) score is an objective method to assess the severity of cirrhosis in this setting. However, calculation of the ALBI score is complex and difficult to access in clinical practice.Recently, the EZ (easy)-ALBI score was proposed as an alternative biomarker of liver injury. We aimed to evaluate the prognostic role of the EZ-ALBI score in HCC from early to advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…11,25 To avoid the complexity of ALBI calculation, the EZ-ALBI score has been proposed with a good correlation with the conventional ALBI score. In our study, the correlation between the EZ-ALBI and ALBI scores was excellent, with a correlation coe cient of 1.000, which was in line with the studies by Kariyama et al and Ho et al 15,16 The prognostic performance of CTP, MELD, and ALBI scores among patients receiving TACE remains unclear in previous studies. [26][27][28][29] In this study, EZ-ALBI and ALBI scores showed high AUROCs and C-indices, which outperformed other models for anticipating death in this population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…11,25 To avoid the complexity of ALBI calculation, the EZ-ALBI score has been proposed with a good correlation with the conventional ALBI score. In our study, the correlation between the EZ-ALBI and ALBI scores was excellent, with a correlation coe cient of 1.000, which was in line with the studies by Kariyama et al and Ho et al 15,16 The prognostic performance of CTP, MELD, and ALBI scores among patients receiving TACE remains unclear in previous studies. [26][27][28][29] In this study, EZ-ALBI and ALBI scores showed high AUROCs and C-indices, which outperformed other models for anticipating death in this population.…”
Section: Discussionsupporting
confidence: 90%
“…15 Further, only 27.0% of patients undergoing TACE were enrolled in the Taiwanese validation set and the study reported a median OS of less than 25 months for patients treated with non-curative treatments, which comprised not only TACE but also systemic treatment and best supportive care. 16 With a small proportion of patients treated with TACE in previous studies, it could not make a rm conclusion for the prognostic performance of EZ-ALBI in patients with intermediate-stage HCC, which usually encompasses a highly heterogeneous population. Moreover, unlike the original Japanese cohort, which mainly comprised of patients with HCV infection (58.6%) 15 , the patients in our study had HBV infection as the majority of liver disease.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, an easy albumin-bilirubin (EZ-ALBI) score, a simplified and user-friendly formula for the ALBI score, has been developed [ 15 ]. EZ-ALBI score was significantly correlated with the conventional ALBI score and demonstrated good prognostic prediction across all HCC stages [ 15 , 16 ]. With its simplicity, the EZ-ALBI score may potentially replace the ALBI score in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, most experts in HCC would agree that the ALBI grade (or easy ALBI grade, an updated version of the ALBI grade) should be entered into the Cox model to generate potential prognostic predictors in this kind of study [6,7]. However, this strategy has not been undertaken in the current study, and pivotal clinical predictors could be missed [1].…”
mentioning
confidence: 99%